2015
DOI: 10.1016/j.expneurol.2015.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Standardization of the experimental autoimmune myasthenia gravis (EAMG) model by immunization of rats with Torpedo californica acetylcholine receptors — Recommendations for methods and experimental designs

Abstract: Myasthenia gravis (MG) with antibodies against the acetylcholine receptor (AChR) is characterized by a chronic, fatigable weakness of voluntary muscles. The production of autoantibodies involves the dysregulation of T cells which provide the environment for the development of autoreactive B cells. The symptoms are caused by destruction of the postsynaptic membrane and degradation of the AChR by IgG autoantibodies, predominantly of the G1 and G3 subclasses. Active immunization of animals with AChR from mammalia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 105 publications
1
56
0
Order By: Relevance
“…Only, a few genes primarily associated with the immune system or inflammation were modified by EAMG, however these were focused on genes that would suppress inflammation. The observation is consistent with histology of muscle of human MG, and EAMG in the chronic stage, which does not have evidence of inflammation (Nakano and Engel, 1993; Losen et al, 2015; Tuzun et al, 2015). The expression of immunosuppressive genes provides the first insight into why EAMG, by extension human MG, lacks inflammatory infiltrates in muscle after the acute induction stage.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Only, a few genes primarily associated with the immune system or inflammation were modified by EAMG, however these were focused on genes that would suppress inflammation. The observation is consistent with histology of muscle of human MG, and EAMG in the chronic stage, which does not have evidence of inflammation (Nakano and Engel, 1993; Losen et al, 2015; Tuzun et al, 2015). The expression of immunosuppressive genes provides the first insight into why EAMG, by extension human MG, lacks inflammatory infiltrates in muscle after the acute induction stage.…”
Section: Discussionsupporting
confidence: 82%
“…The rat and human immune systems possess unique characteristics, and the exogenous administration of autoantigen with adjuvant does not mimic the spontaneous development of the breakdown in tolerance of the human disease (Losen et al, 2015). However, the ultimate common pathway of antibody attack with complement activation is shared between EAMG and human MG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 They showed that rabbits immunized with AChR protein purified from the Electrophorus electricus electric organ developed MGlike symptoms, with flaccid paralysis and decremental electromyographic response. 21 Immunized rats show transient muscle weakness with high frequency after approximately 7 days. Subsequent to the publication of that pivotal study, mice and rats have been used for the induction of AChR-EAMG, and rats were found to be more susceptible than mice, with a high incidence of clinical signs of the disease.…”
Section: Animal Models Of Achr-mgmentioning
confidence: 99%
“…In this model, the animals mount an active immune response against injected AChR, and MG is caused by cross-reactions of the antibodies with the animals' own muscle AChR. [21][22][23] Nevertheless, the mouse model has an advantage for the elucidation of MG pathogenesis due to the availability of diverse transgenic, knockout and mutant mouse strains. 20 In rats, EAMG can be induced by single immunization with AChR protein purified from Torpedo californica and emulsified in complete Freund's adjuvant.…”
Section: Animal Models Of Achr-mgmentioning
confidence: 99%